Shirin Ebadi, cita-cita sang hawa di tanah bangsa Arya (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
The progress of the Iranian state is not directly proportional to the realization of civil rights between men and women. One of the women who has a special concern for women’s issues in Iran is Shirin Ebadi, a human rights activist from Iran, she tries to fight for and restore what is right for herself and other members of society. The main problem raised in this study is How the Role of Shirin Ebadi in the Issue of Women’s Rights in Iran (Review of Social Aspects of 1990-2003)? The methods used were including source collection, source criticism, interpretation, and historiography. The results of the research can be explained that the role of Shirin Ebadi has an impact on the lives of women in Iran, the parliament seats which were originally filled by men, now women have begun to be involved in the political world in Iran. Regime change seems to have never been the initial milestone for elimination of violence against women in Iran. The idea of establishing a Defend of Human Rights Center is very important for Shirin as a forum for women or children who are victims of human rights injustice in Iran.
Keywords: Shirin Ebadi; Gender injustice; Iran